2008
DOI: 10.1109/isscc.2008.4523220
|View full text |Cite
|
Sign up to set email alerts
|

A 32kb 10T Subthreshold SRAM Array with Bit-Interleaving and Differential Read Scheme in 90nm CMOS

Abstract: Abstract-Ultra-low voltage operation of memory cells has become a topic of much interest due to its applications in very low energy computing and communications. However, due to parameter variations in scaled technologies, stable operation of SRAMs is critical for the success of low-voltage SRAMs. It has been shown that conventional 6T SRAMs fail to achieve reliable subthreshold operation. Hence, researchers have considered different configuration SRAMs for subthreshold operations having single-ended 8T or 10T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 3 publications
0
52
0
Order By: Relevance
“…Recently, a number of works [1][2][3][4] have shown aggressive supply voltage reduction to near or below the threshold voltage (Vth) of MOSFET devices with considerable reduction in power consumption. However, this power improvement has come at the cost of operation speed (typically <10 MHz).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of works [1][2][3][4] have shown aggressive supply voltage reduction to near or below the threshold voltage (Vth) of MOSFET devices with considerable reduction in power consumption. However, this power improvement has come at the cost of operation speed (typically <10 MHz).…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 3 plots the change in power consumption of low-power LSI chips reported from 2007 to 2014 at ISSCC and VLSI Circuits [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37], which are the most popular international conferences in the semiconductor industry. It is found that there are three domains: milliwatt, microwatt, and nanowatt.…”
Section: Trends In Circuit Technology and Energy Harvestingmentioning
confidence: 99%
“…Thus many works have been carried out on the subthreshold operation of logic circuits 3)-7) and SRAM's 8) , where V DD is less than V TH of transistors. However, the number of transistors of the previously reported subthreshold circuits is small (e.g., 70 k transistor logic circuits at V DD of 230 mV 3) , a 32 kbit SRAM at V DD of 160 mV 8) , and a 1000 stage inverter chain at V DD of 60 mV 6) ), and the possibility of the mega gate scale subthreshold circuits is not clear.…”
Section: Fine-grain Body Bias Control To Reduce V Ddminmentioning
confidence: 99%